From Tradition to Transformation: Development of an Approach for Business Model Adaptation in Automotive Supplier SMEs - Anello, Marco; Kölmel, Bernhard; Waidelich, Lukas (Digital Technologies Research and Applications, 2025)
The automotive industry is undergoing a profound transformation driven by electrification, digitalization, and evolving value chains. Small and medium‑sized enterprises (SMEs) in the supplier sector face particular challenges in adapting their business models to these changes. This study addresses this issue by developing the PIC approach, a structured process model consisting of three phases: Preparation, Implementation, and Control. Based on a systematic literature review, the model integrates theoretical insights with practical tools tailored to SMEs. A fictitious case study demonstrates the applicability of the approach and illustrates how companies can use it to assess their current state, define a strategic direction, and manage the transformation process. Continuous improvement is supported through the integration of continuous improvement process principles. While the PIC model is conceptual in nature, it offers a promising foundation for practical application. The objective of this approach is to support successful adaptation, helping users address challenges and mitigate risks arising from ongoing changes in the automotive sector. This work is carried out within the TraFoNetz project—a regional initiative in Germany’s Northern Black Forest that supports the transformation of SMEs in the automotive supply industry. Future research will focus on validating the approach in real‑world settings and refining it further.